NILAI TAMBAH DAN PENDAPATAN PENGOLAHAN KERIPIK BELUT - Yasinta Renyanita Sueng,; Nyoman Utari Vipriyanti,; Putu Fajar Kartika Lestari, (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2023)
One of the fishery products is eel, where eel can be processed into eel. The purpose of this study is to : analyze the added value and income obtained from processing eel into eel chips in Mengwitani Village, Mengwi District, Badung Regency. This research was conducted at UD Indra Dwi Ananda in Mengwitani Village, Mengwi District, Badung Regency. The research period is two months from September to October 2022. The types of data used in the study include qualitative data and quantitative data. Sources of data in this study are primary data and secondary data. The method used by respondents is the census method, which uses the entire population as respondents who operate as many as 9 people. Data collection methods include: observation, interviews, questionnaires, and documentation. The results showed that the added value generated from processing eel into eel chips in one production process at UD Indra Dwi Ananda, Mengwitani Village, Mengwi District, Badung Regency was Rp. 28.800 per kilogram with a total production of 60 kilograms of eel chips in one time. production process. The income received from processing eels into eel chips in one production process at UD Indra Dwi Ananda in Mengwi Village, Mengwi District, Badung Regency is Rp. 2.800.833 or Rp. 22.406.664 per However, it can be suggested to the government and related agencies to intensify their attention and guidance which includes aspects of capital technology management and marketing because there is added value and the opinion generated from processing eel into eel chips is quite high UD Indra Dwi Ananda in Mengwitani Village, Mengwi District, Badung Regency, hopefully more developed in the future.